Design and build teledentistry applications based on the appstore playstore on the management of dental practice during the Covid-19 pandemic and adapting new habits: Rancang bangun aplikasi teledentistry berbasis appstore dan playstore pada manajemen praktik dokter gigi selama pandemi Covid-19 dan adaptasi kebiasaan baru - Fuad Husain Akbar (Makassar Dental Journal PDGI Makassar, 2022)
Health is one of the basic needs of every human being. Covid-19 pandemic has challenged existing healthcare systems around the world, so the development of information technology is increasing. This article is aimed to create a teledentistry applica-tion based on the appstore and playstore for dental practice during the Covid-19 pandemic. Implementation method includes conducting literature studies, requirements engineering, system design, system implementation anddrawing conclusions and suggestions. The result show tested functionality on application features is directly proportional to the expected result. It was concluded that the design of an android-based teledentistry application in dental practice can simplify the service process, help increase time effectiveness in the dental clinic service process, increase the efficiency of the recording system in dental clinic services quickly and accurately. And the design of this system canhelp minimize losses due to errors in recording patient data.